SISENSI: QR Code-based Academic Attendace System - Arif Setiawan; Dwi Nur Fitria Agustin Rahayu (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Presence is something that cannot be separated from the learning process, it becomes motivation and discipline information for every activity in it. This study aims to develop a QR Code-based academic attendance application that can be used by Informatics Engineering Education students. The research method used is R&D (Research and Development) using the RAD (Rapid application development) development model. Application development made using Kodular and Moodle. This application contains a QR Code scan menu as the main focus in this media as well as other supporting menus in the form of virtual tours, news, timetables, and UMS stars. In the process of developing this application, several tests were carried out, namely functionality testing using blackbox, usability testing using the SUS (system usability scale) instrument, reliability testing and application compatibility testing using the firebase test lab. used based on the validation carried out by experts as many as three experts from Informatics Engineering Education lecturers and trials given to users as many as thirty-five students from the Informatics Engineering Education study program, it can be said that the application is suitable for use by Informatics Engineering Education students.